2021
DOI: 10.4049/jimmunol.2000239
|View full text |Cite
|
Sign up to set email alerts
|

Gut Bacteria Induce Granzyme B Expression in Human Colonic ILC3s In Vitro in an IL-15–Dependent Manner

Abstract: Group 3 innate lymphoid cells (ILC3s) in the gut mucosa have long been thought to be noncytotoxic lymphocytes that are critical for homeostasis of intestinal epithelial cells through secretion of IL-22. Recent work using human tonsillar cells demonstrated that ILC3s exposed to exogenous inflammatory cytokines for a long period of time acquired expression of granzyme B, suggesting that under pathological conditions ILC3s may become cytotoxic. We hypothesized that inflammation associated with bacterial exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…These data suggest that Granzyme B might have other functions, alternative to inducing target cell apoptosis. It was recently shown that ILC3s from the gut were able to express Granzyme B upon bacterial stimulation ( 48 ). Furthermore, Granzyme B has the ability to remodel the extracellular matrix by inducing anoikis and detachment of tumor cells, which prevents tumor cell migration and invasion ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that Granzyme B might have other functions, alternative to inducing target cell apoptosis. It was recently shown that ILC3s from the gut were able to express Granzyme B upon bacterial stimulation ( 48 ). Furthermore, Granzyme B has the ability to remodel the extracellular matrix by inducing anoikis and detachment of tumor cells, which prevents tumor cell migration and invasion ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, granzyme B expression of ILC3s is increased, with some ILC3 subsets even co-expressing perforin to exert a cytotoxic effect similar to NK cells ( Fig. 1 ) ( 42 ).…”
Section: Introductionmentioning
confidence: 99%